(3TQM GdHSGeI HCWhGb GdMeGeIs - (3YHO Gdedc Hf YHO Gddg Hf HOQhf, CHh GdbGSe GdMVQej Ke GdTdHj,J (B608 (3g` s
(3ChdgG (B:s
(3aEfg LeYfi jheG ef GdCjGe eY LeGYI hOYG Edi GdEaGVI ai gPG GdTCf hfOH , aCaVfG bOGM GdePGcQI ai GdCOH aCfTO CMO GdMGVjf bUjOI GdhRjQ MJi cGf ajge ef bGd (B: (3eG gPg GdbUjOI EdG cGdeYei s
(3BNQgG (B:s
(3ced GdcJGH HJeGe GdbUjOI s
(3hgj bUjOI CHj eMeO YHO GdeLjO Hf YHOhf GdagQi GdeJhai SfI (B520(3g`s
(3hGdeDda cGf MjG SfI (B608(3g` hHGdebOeI HjGV ai CcKQ ef ehVYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B161 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B184s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN C (B- (3bSe (B4 - (3U (B249 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs